Representing and Recommending Shopping Baskets with Complementarity, Compatibility, and Loyalty - Wan, Mengting; Wang, Di; Liu, Jie; Bennett, Paul; McAuley, Julian (27th ACM International Conference on Information and Knoweldge Management, 2018)
We study the problem of representing and recommending products for grocery shopping. We carefully investigate grocery transaction data and observe three important patterns: products within the same basket complement each other in terms of functionality (complementarity); users tend to purchase products that match their preferences(compatibility);and a significant fraction of users repeatedly purchase the same products overtime (loyalty). Unlike conventional e-commerce settings, complementarity and loyalty are particularly predominant in the grocery shopping domain. This motivates a new representation learning approach to leverage complementarity and compatibility holistically, as well as a new recommendation approach to explicitly account for users "must-buy" purchases in addition to their overall preferences and needs. Doing so not only improves product classification and recommendation performance on both public and proprietary transaction data covering various grocery store types, but also reveals interesting findings about the relationships between preferences, necessity, and loyalty in consumer purchases.